2011
DOI: 10.1007/s10974-011-9256-7
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate has dual, independent effects on the cardiac sarcoplasmic reticulum/endoplasmic reticulum Ca2+ ATPase

Abstract: We determined the effects of epigallocatechin-3-gallate (EGCG) and epicatechin (EC), on pump turnover and Ca2+ transport by the cardiac form of the sarcoplasmic/endoplasmic reticulum Ca2+-ATPase (SERCA). Fluorescence spectroscopy was used to directly measure SERCA ATPase activity and to measure Ca2+ uptake into cardiac sarcoplasmic reticulum (SR) vesicles and microsomes derived from human embryonic kidney (HEK) cells expressing human cardiac SERCA2a. We found that EGCG reduces the maximum velocity of Ca2+ upta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
3
4
0
Order By: Relevance
“…This finding is consistent with another independent report, demonstrating that no significant effect on SERCA2 activity was observed with EGCG at a concentration Ͻ4.8 M (Kargacin et al, 2011). Ca 2ϩ influx via L-type Ca 2ϩ channels triggers Ca 2ϩ release from the SR (Nä bauer et al, 1989).…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with another independent report, demonstrating that no significant effect on SERCA2 activity was observed with EGCG at a concentration Ͻ4.8 M (Kargacin et al, 2011). Ca 2ϩ influx via L-type Ca 2ϩ channels triggers Ca 2ϩ release from the SR (Nä bauer et al, 1989).…”
Section: Discussionsupporting
confidence: 93%
“…Dephosphorylated PLB interacts with SERCA2 and inhibits the pumping activity, whereas phosphorylation of PLB relieves the inhibitory effects resulting in increased calcium re-uptake into the SR and enhanced contractility [46], as we actually observed. On the other hand, our observations are consistent with data published by Kargacin et al [7] who demonstrated that EGCG increases SR Ca 2+ uptake by altering the transmembrane interaction between SERCA2 and PLB, which in turn depends on the phosphorylation status of the latter. It is well known that the cardiac excitation-contraction coupling is highly dependent on Ca 2+ transient, that is handled through an array of ion channels, antiporters and pumps that are finally regulated, at post-translational level, by phosphorylation.…”
Section: Cellular Physiology and Biochemistrysupporting
confidence: 93%
“…Mechanistic studies have demonstrated that tea polyphenols may influence many aspects of cardiovascular function by their interaction with a list of intracellular target sites, such as several ion channels and ion exchangers (Na ), intracellular Ca 2+ storage, and sarcomeric Troponin protein [7,13,15]. Another study reported that EGCG acute administration in cardiomyocytes, isolated from a transgenic mice model of hypertrophic cardiomyopathy, ameliorated sarcomere shortening and lowered relaxation time by decreasing the thin myofilament Ca 2+ sensitivity [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We therefore assume that at this concentration EGCg does not increase sarcoplasmic reticulum (SR) Ca 2+ load. Data from canine SR vesicles and HEK293 cell microsomes show that EGCg concentrations > 4.8 μM directly inhibit SR calcium ATPase (Kargacin et al, 2011). Additionally, Feng et al reported no effect on SERCA in rabbit cardiac and skeletal SR membranes with 1–2 μM EGCg (Feng et al, 2012; Najafi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%